Automated Line for Post-Harvest Processing of Root Crops and Potatoes - A. S. Dorokhov; M. A. Mosyakov; N. V. Sazonov (Сельскохозяйственные машины и технологии)
In the process of post-harvest processing of root crops and potatoes in Russia, mechanical sortings of various types are used, which allows to separate the material according to the size criterion and removing impurities. The main requirement for this equipment is to ensure the quality and reliability of technological processes for the impurities separation and the root crops separation into fractions with minimal damage. (Research purpose) To improve the quality of potato tubers sorting using an automated line for post-harvest processing of root crops and potatoes, which allows to reduce their damage and ensure high accuracy of separation into fractions by size. (Materials and methods) The authors studied the automated process of root crops post-harvest processing. They developed approaches and basic technical, technological and constructive solutions aimed at improving the efficiency of root crops and potatoes post-harvest processing. To automate the root crops and potatoes processing, the authors installed the universal web camera Logitech HD Pro C920. They created a basic block diagram of the electronic line system operation. (Results and discussion) The authors clarified the size and mass characteristics of potato tubers with a total weight of 38 356 grams of Nevsky variety of the 2019 harvest and their shape coefficient. They developed design documentation. An experimental line was prepared for potato tubers post-harvest sorting with an original circuit diagram of the electronic system operation. The authors substantiated its design and operational-technological parameters. Practical studies of the automated line work were carried out in the Ryazan region on the basis of the Institute of Seed Production and Agrotechnologies – a branch of the Federal Scientific Agroengineering Center VIM. (Conclusions) The authors determined that the developed automated line for root crops and potatoes post-harvest sorting thanks to digital technologies reduced labor costs by eliminating manual sorting, as well as improving the quality of potato tubers and the accuracy of sorting by size to 95-98 percent. It was revealed that damage to potato tubers did not exceed one percent.